Genetic susceptibility to prostate cancer in Taiwan: A genome‐wide association study - Bau, Da‐Tian; Tsai, Chia‐Wen; Chang, Wen‐Shin; Yang, Jai‐Sing; Liu, Ting‐Yuan; Lu, Hsing‐Fang; Wang, Yu‐Wen; Tsai, Fuu‐Jen (Molecular carcinogenesis, 2024)
We conducted the first genome‐wide association study (GWAS) of prostate cancer (PCa) in Taiwan with 1844 cases and 80,709 controls. Thirteen independent single‐nucleotide polymorphisms (SNPs) reached genome‐wide significance (p < 5 × 10−8). Among these, three were distinct from previously identified loci: rs76072851 in CORO2B gene (15q23), odds ratio (OR) = 1.54, 95% confidence interval (CI), 1.36–1.76, p = 5.30 × 10−11; rs7837051, near two long noncoding RNA (lncRNA) genes, PRNCR1 and PCAT2 (8q24.21), OR = 1.41 (95% CI, 1.31–1.51), p = 8.77 × 10−21; and rs56339048, near an lncRNA gene, CASC8 (8q24.21), OR = 1.25 (95% CI, 1.16–1.35), p = 2.14 × 10−8. We refined the lead SNPs for two previously identified SNPs in Taiwanese: rs13255059 (near CASC8), p = 9.02 × 10−43, and rs1456315 (inside PRNCR1), p = 4.33 × 10−42. We confirmed 35 out of 49 GWAS‐identified East Asian PCa susceptibility SNPs. In addition, we identified two SNPs more specific to Taiwanese than East Asians: rs34295433 in LAMC1 (1q25.3) and rs6853490 in PDLIM5 (4q22.3). A weighted genetic risk score (GRS) was developed using the 40 validated SNPs and the area under the receiver‐operating characteristic curve for the GRS to predict PCa was 0.67 (95% CI, 0.63–0.71). These identified SNPs provide valuable insights into the molecular mechanisms of prostate carcinogenesis in Taiwan and underscore the significant role of genetic susceptibility in regional differences in PCa incidence.